THE POSITION OF INTEREST IN SPORTS AND RECREATION OF 7th GRADE ELEMENTARY SCHOOL STUDENTS IN THE FACTOR ANALYSIS OF DIFFERENT INTEREST - Vladimir Milošević; Adam Petrović; Nikola Stevanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Personal interests carry a great potential and are usually a drive to act. Therefore they usually point towards the activity of an individual in his interest area. An insight into the position of the interest in sports and recreation among other interests can be obtained by inspecting the interests of 7th grade elementary school students from Sremska Mitrovica and Jagodina. The sample consisted of 736 7th grade elementary school students of both genders. A non-experimental study of the students' interests was done using a questionnaire that consisted of 5 interest indicators: job preference, self-estimation of affinity, use of free time, direct self-estimation of interests and reaction to key words-stimuli. Each indicator had 30 items that asses 30 interests. A t test was used to inspect the level of interest in sports and recreation. Also, factor analysis was done for each indicator separately. The reason for this approach is that there is no real confirmation that these 5 indicators are well suited for assessing the interests of young persons in the time we live in. Students' interest in sports and recreation is about 4 on the scale of 1 to 5, on each of the indicators. The data shows that the interest of 7th grade elementary school students in sports and recreation is closely linked to interest in military, these two interests belong to the same factor regardless of the way the interests are assessed, that is, they belong to the same factor on each of the 5 indicators. The interest in adventure belongs to the same factor as the interest in sports and recreation on 4 out of 5 indicators, and interest in humor, interest in travel and hedonistic interest on 3 out of 5 indicators. These results might indicate that the motives for engaging in sports and recreation are unstable, because this composition of relatedness of the interests can be interpreted as the factor of fun. If that is so, these findings alert to the importance of building a system of human values in which the physical education, taken in a broader sense, will have a significant place. A high level of students' interest in sports and education is a good starting point for reflecting upon the practice in the system of physical education and the system of sports of young persons. However, we must bear in mind the structure of interests. Professionals in the physical education area are obligated by the interests' value orientation to positively influence the youth.